Regulatory experimentation in energy: Three pioneer countries and lessons for the green transition. (September 2021) - Schittekatte, Tim; Meeus, Leonardo; Jamasb, Tooraj; Llorca, Manuel
Abstract: Regulatory experimentation is a novel approach to enable innovation in the energy sector, while maintaining the protection of consumers. We define regulatory experimentation as a temporary removal of regulatory barriers. This can be in the form of a derogation from a rule, but it can also mean assigning responsibility to players to conduct activities that they are normally not allowed to engage in. The outcomes of regulatory experiments inform future regulation. In this paper, we discuss experiences with regulatory experimentation in the energy sector of three pioneering countries: the Netherlands, Great Britain, and Italy. We compare the implementations along six design dimensions: eligible project promoters, scope of the derogations, length of the derogations, administration of the experiments, the access to public funding, and transparency. We also discuss how the early approaches have evolved in these countries. Finally, we look ahead and discuss how regulatory experimentation can evolve in the future European context to contribute to the green transition. Highlights: Regulatory experimentation is a new approach to enable innovation in the energy sector. We introduce a six design dimension framework to analyse different approaches. We compare implementations in the Netherlands, Great Britain, and Italy. We discuss how regulatory experimentation can evolve in the European context.